Efficacy of Nx4 to Reduce Plasma Cortisol and Gastrin Levels in Norwegian Sled Dogs During an Exercise Induced Stress Response: A Prospective, Randomized, Double Blinded, Placebo-Controlled Cohort Study - Keller, Alexandra; Conradi, Jana; Weber, Corinna; Failing, Klaus; Wergin, Melanie (Frontiers in Veterinary Science, 2021)
An exercise induced stress response is commonly seen in high performance sled dogs, resulting in increased plasma cortisol. A stress induced rise of cortisol might result in increased prevalence of gastritis and gastric ulcers mediated by an increased gastrin. Neurexan® (Nx4) is a medicinal product used for stress relief by reduction of cortisol. The aim of the study was to show that Nx4 reduces plasma cortisol and plasma gastrin in high performance sled dogs and to show tolerability of Nx4 in dogs. First, a pilot study was done to validate the increase of cortisol by performance. The data from the pilot study was used for sample size estimation via an adapted power analysis as well as the identification of important prognostic variables. These were then used in the randomization procedure of the main study. Second, a prospective randomized, double blinded, placebo-controlled cohort study was conducted. The main study included 45 sled dogs, assigning 23 dogs to the Nx4 group and 22 dogs to the placebo group, to analyze plasma cortisol and plasma gastrin at four time points: before, directly after and 30min and 120min after performance. For the main target variable, area under the curve (AUC) of plasma cortisol, a significantly lower adjusted mean value in the Nx4 group compared to the placebo group (p=0.031) was found. Plasma gastrin was also significantly reduced in the Nx4 group 30 min after performance (p=0.023), resulting in a significantly reduced plasma gastrin AUC in the Nx4 group compared to the placebo group (p=0.049) Within the limitation of the study, the results carry implications for the usefulness of Nx4 to reduce exercise induced plasma cortisol and gastrin levels. The reduction of the exercise induced stress response could help to improve the welfare of high-performance sled dogs. Since activation of the hypothalamic-pituitary-adrenal axis resulting in increased cortisol is similar for exercise induced stress and psychologic stress, the same might be true independent of the stressor, making Nx4 potentially useful in any stressful situation for dogs.